Crotalus durissus terrificus (viperidae; crotalinae) envenomation: Respiratory failure and treatment with antivipmyn TRI® antivenom. (May 2019) - Baum, R.A.; Bronner, J.; Akpunonu, P.D.S.; Plott, J.; Bailey, A.M.; Keyler, D.E.
Abstract: We report an envenomation to a professional herpetologist by a South American rattlesnake ( Crotalus durissus terrificus) that resulted in respiratory failure, and therapeutic improvement following antivenom administration. A 56-year-old male was bitten on the left wrist by a Crotalus durissus terrificus ( C. d. terrificus ) while attempting to tube the snake for maintaining safe control while performing venom extraction . The patient was intubated due to rapidly ensuing respiratory failure and administration of Antivipmyn-TRI® was initiated while being transported via ambulance. The patient was admitted to the hospital unconscious and unresponsive. Mechanical ventilation was required until 5 h after completion of antivenom administration. No significant adverse effects were observed with antivenom administration. The patient was discharged approximately 55 h following envenomation. This is the first reported case in the United States of a patient following a C. d. terrificus envenomation with consequent respiratory failure, and in which Antivipmyn-TRI® was successfully administered. Highlights: South American rattlesnake envenomation to professional herpetologists is a rare event. C.d. terrificus is a medically important subspecies uncommon in USA zoos. Rapid respiratory failure following envenomation by an adult C.d. terrificus. Crotoxin, a major presynaptic neurotoxin is responsible for progressive paralysis.